Towards the Prevention of Youth Homelessness - Stephen Gaetz; Amanda Buchnea; Cathy Fournier; Erin Dej; Kaitlin Schwan (Youth)
Historically, the prevention of youth homelessness has not been a priority in Canada or the United States. In recent years, this has begun to change. While there is growing recognition that a shift by preventing homelessness is required to bring a substantive end to homelessness, a common and shared understanding of what prevention is and what it involves has remained largely absent or obscured in both policy and practice. In this paper, we focus specifically on the prevention of youth homelessness and set out to provide conceptual clarity through presenting a clear definition of what prevention is and what it is not. Accompanying the definition is a five-point typology that includes (1) structural prevention; (2) systems prevention; (3) early intervention; (4) crisis intervention, and (5) housing stabilization. Each of the five elements of the typology is defined, identifying who is responsible for implementation. In addition, the typology is populated with examples of different approaches to the prevention of youth homelessness. We conclude with some key considerations to guide the implementation of preventive interventions and present core principles designed to support the development of effective and quality prevention interventions.